1983
DOI: 10.2527/jas1983.571168x
|View full text |Cite
|
Sign up to set email alerts
|

Monensin Effects on Digestibility, Methanogenesis and Heat Increment of a Cracked Corn-Silage Diet Fed to Steers

Abstract: Six 300-kg steers were each fed a 70% cracked corn plus corn silage diet at two levels of intake above maintenance with and without 3 mg monensin/kg.75 body weight (W.75). A changeover design was used. Dietary energy and nitrogen were partitioned by duplicate, 22-h indirect respiration calorimetry measurements of heat and methane production on each animal concurrent with 7-d total feces and urine collection trials. Feed and feces were analyzed for energy, N, starch and neutral detergent fiber (NDF). The partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
2
15

Year Published

1993
1993
2010
2010

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 0 publications
5
29
2
15
Order By: Relevance
“…However, the effect of monensin on digestion has been inconsistent in the past. In various in vitro and in vivo studies, monensin has been reported to depress (Poos et al 1979;Mir 1989), to affect minimally (Dinius et al 1976;Lemenager et al 1978;Ricke et al 1984;Faulkner et al 1985) or not at all (Kone and Galyean 1990;Duff et al 1995), and even to increase (Wedegaertner and Johnson 1983) fiber digestibility. Factors such as daily dosage of monensin, ratio of forage to concentrate consumed and differences in ruminal dilution rates or retention times of digesta (Lemenager et al 1978) may also account for this variability.…”
Section: Monensinmentioning
confidence: 99%
“…However, the effect of monensin on digestion has been inconsistent in the past. In various in vitro and in vivo studies, monensin has been reported to depress (Poos et al 1979;Mir 1989), to affect minimally (Dinius et al 1976;Lemenager et al 1978;Ricke et al 1984;Faulkner et al 1985) or not at all (Kone and Galyean 1990;Duff et al 1995), and even to increase (Wedegaertner and Johnson 1983) fiber digestibility. Factors such as daily dosage of monensin, ratio of forage to concentrate consumed and differences in ruminal dilution rates or retention times of digesta (Lemenager et al 1978) may also account for this variability.…”
Section: Monensinmentioning
confidence: 99%
“…Nesses ensaios, independentemente do regime alimentar, a eficiência alimentar também melhorou. Outras influências da monensina em animais em confinamento são: redução na relação acetato:propionato (Raun, 1992), aumento da concentração de ácido propiônico, diminuição da produção de metano e amônia (Badawy et al, 1996), melhora na digestibilidade dos alimentos (Wedegaertner & Johnson, 1983) e controle de coccidiose (Paisley & Horn, 1996). Aparentemente, em todos os experimentos, o aumento da energia disponível, favorecido principalmente pela elevação do ácido propiônico, e a redução da produção dos gases metano e carbônico, diminuíram o consumo (melhorando a digestibilidade) nos animais, em decorrência de uma regulação do balanço Médias seguidas de letras iguais, na linha, não diferem (P>0,05) entre si pelo teste Tukey.…”
Section: Resultsunclassified
“…The toxicity of the ionophores to determined microorganisms can reduce the energetic loss of the diet through enteric methane production. Wedegaertner & Johnson (1983) observed that the effect of monensin in the reduction of the methane production and the loss of energy in the faeces and urine increased the retention of energy in bovines by 19%. Moreover, the methane expelled by the ruminants is presently the focus of criticism, since it presents a greenhouse effect 21 times greater than CO 2 (UNFCC, 2005), a lifespan of 14 years in the atmosphere (IPCC, 1995) and an annual emission estimate, of the Brazilian herd alone, of 9.38 Tg of CH 4 /year (MCT, 2006).…”
Section: Introductionmentioning
confidence: 99%